Possibilities to recycle plastic waste in cementitious materials - Vaičienė, Marija; Malaiškienė, Jurgita (International Conference “Environmental Engineering”, 2020)
In the paper, the changes of properties of expanded clay concrete when a part of the coarse aggregate is replaced with plastic waste are discussed upon. First of all, standard expanded clay concrete specimens were formed, and then 5%, 10%, 20% share of the fraction 4/8 of the expanded clay aggregate was replaced with plastic waste. The properties of expanded clay concrete, such as the density of the mixture, the slump, the density of the dried expanded clay concrete specimens, the ultrasonic pulse velocity, the water absorption, and the compressive strength, were established and analyzed; in addition, a microstructural examination was carried out. It was found that upon striving to use the maximum share of waste (20%), it is possible to ensure about 4% higher density of expanded clay concrete and almost 50% higher compressive strength, as compared to expanded clay concrete of the control specimens. SEM analysis showed that the same minerals, i.e. portlandite, ettringite, calcite and calcium hydro silicates were identified in specimens from all batches.